1974
DOI: 10.1113/jphysiol.1974.sp010558
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and morphological identification of hypothalamic magnocellular neuroendocrine cells in goldfish preoptic nucleus*

Abstract: SUMMARY1. Intracellular recordings were made from antidromically identified neurones in the goldfish preoptic nucleus and Procion Yellow was ejected from the recording pipette, marking these magnocellular neuroendocrine cells diffusely, for histological identification.2. In confirmation of earlier studies these preoptic neuroendocrine cells showed resting membrane potentials of 47 mV, action potentials up to 85 mV, action potentials of long duration (3.9 msec) occurring in two steps, long-lasting hyperpolarizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…The electrophysiological properties of enkephalin neurons from this study are consistent with previous findings of MgC of the goldfish (3,4,11,14) and mammalian hypothalamus (18) and in other mammalian central neurons (19). On the basis of these initial electrophysiological and morphological data, enkephalin neurons cannot be distinguished either functionally or structurally from the isotocin or vasotocin MgC also present in the NPO of the goldfish (2,4,20).…”
Section: ) Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The electrophysiological properties of enkephalin neurons from this study are consistent with previous findings of MgC of the goldfish (3,4,11,14) and mammalian hypothalamus (18) and in other mammalian central neurons (19). On the basis of these initial electrophysiological and morphological data, enkephalin neurons cannot be distinguished either functionally or structurally from the isotocin or vasotocin MgC also present in the NPO of the goldfish (2,4,20).…”
Section: ) Discussionsupporting
confidence: 91%
“…Adult goldfish (Carassius auratus), weighing 290-850 g and measuring 25-35 cm, were anesthetized, immobilized, suspended, and perfused with water, and the brain was exposed according to earlier methods (11,14).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scanning electron microscopic observations have shown that the surface of the choroid plexus and distinct areas known as the circumventricular 80 PRIMATE OSMORECEPTOR AND ADH RELEASE organs are free of cilia, while major parts of the ventricular ependyma are covered by a dense layer of cilia in rabbit, cat and squirrel monkey (Weindl & Joynt, 1972). Many workers have attributed a sensory function to the processes of magnocellular neurosecretory cells ending freely in the ependyma of the third ventricle of fishes and amphibia (Dierickx, 1962;Smoller, 1965;Hayward, 1974). On the basis of the present data as well as the considerable histological evidence (see above), it is proposed that the osmoreceptors of Verney are sodium sensitive elements composed of the ependymal dendrites alone or specialized ependymal cells plus the dendrites in the anterior third ventricle.…”
Section: Discussionmentioning
confidence: 66%